Diabetes in people with an intellectual disability: a systematic review of prevalence, incidence and impact. Issue 8 (August 2014) - McVilly, K.; McGillivray, J.; Curtis, A.; Lehmann, J.; Morrish, L.; Speight, J.
Abstract Aims To establish the prevalence and incidence of Type 1 and Type 2 diabetes in people with an intellectual and developmental disability and determine their impact on health and well‐being and to appraise the evidence available to inform good practice in diabetes management for people with intellectual and developmental disabilities. Methods We conducted separate searches of multiple databases (EMBASE, CINAHL, MEDLINE, PsycINFO, SCOPUS, Web of Science, PUBMED and Cochrane Library) to find relevant articles. Results A total of 13 studies were identified: 13 addressed the prevalence of diabetes in people with intellectual and developmental disability, three addressed the impact of diabetes on their health and well‐being and three addressed the management of diabetes. The prevalence of diabetes in people with intellectual and developmental disability remains uncertain, and the incidence of diabetes in this group of people is unknown. There is some evidence to support the assertion that people with intellectual and developmental disability might be at greater risk of diabetes than the general population. Overall, the quality of the evidence on which to base prevention and management strategies is variable. Conclusions There is a paucity of research focusing on the prevalence, incidence and impact of diabetes among people with intellectual and developmental disability. Further research is needed to inform policy and practice in this area and, in particular, work is needed to develop methodologies, evaluation tools, educational resources and diabetes care support services appropriate to the needs of people with intellectual and developmental disability.